THE PROBLEM OF STUDYING THE LYRICS OF RUSSIAN POETS IN THE UZBEK SCHOOL (ON THE EXAMPLE OF THE CREATIVITY OF S. YESENINA) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article deals with the problems of studying lyrics in the Uzbek school. Some difficulties related to the complexity of the perception of the lyrical text by Uzbek students are noted.